2016
DOI: 10.4269/ajtmh.15-0496
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Environmental Surveillance for Vibrio cholerae in Resource Constrained Areas: Application During a 1-Year Surveillance in the Far North Region of Cameroon

Abstract: Biological confirmation of the presence of Vibrio cholerae in clinical and environmental samples is often constrained due to resource- and labor-intensive gold standard methods. To develop low-cost, simple, and sustainable surveillance techniques, we modified previously published specimen sampling and culture techniques and applied the use of enriched dipstick testing in conjunction with the use of filter paper for DNA specimen preservation during clinical and environmental surveillance in the Far North of Cam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
63
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 18 publications
1
63
0
Order By: Relevance
“…This field evaluation of the enriched rapid test for diagnosis of cholera confirmed initial reports suggesting that the APW incubation step ensures high specificity, which improves confidence in the test results and could diminish the risk of false cholera outbreak alerts [13,14]. Incubation in APW for 4–6 hours is also the first step in laboratory methods used for the diagnosis of V .…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…This field evaluation of the enriched rapid test for diagnosis of cholera confirmed initial reports suggesting that the APW incubation step ensures high specificity, which improves confidence in the test results and could diminish the risk of false cholera outbreak alerts [13,14]. Incubation in APW for 4–6 hours is also the first step in laboratory methods used for the diagnosis of V .…”
Section: Discussionsupporting
confidence: 63%
“…However, in this study, the performance of the direct test was not consistent with previously published studies, with low sensitivity (65%) and high specificity (92%); the reasons for these discrepancies were not discussed, but could be due to the addition of a step of dilution of the stools in a sample preparation vial. Another study confirmed the high specificity of RDT after enrichment in APW but sensitivity could not be reliably estimated due to the low number of confirmed cholera cases [14]. …”
Section: Introductionmentioning
confidence: 99%
“…Beyond the recent study in Bangladesh, there is only one other study to our knowledge that has used the Crystal VC ® dipstick test for the detection of V. cholerae in water. This study, conducted in Northern Cameroon, found a specificity of 100% in comparison with PCR, but had insufficient numbers of positive water samples to calculate sensitivity .…”
Section: Discussionmentioning
confidence: 83%
“…Culturing is considered to be the gold standard for detecting V. cholerae but requires skilled technicians and a laboratory facility, which is often not feasible in resource-limited settings [9][10][11][12]. Recently, a rapid dipstick test, for detection of V. cholerae (Crystal VC â kit, Span Diagnostics Ltd., Surat, India), was introduced and validated for detecting the pathogen from stool and environmental water samples [13][14][15][16][17][18][19][20]. However, to our knowledge, no study has been carried out to validate the use of this dipstick test for conducting household surveillance of V. cholerae in stored water samples.…”
Section: Introductionmentioning
confidence: 99%
“…The audience learned from Martin Mengel, from Agence Medicine Preventive, Paris, that further efforts to understand the distribution of cholera in Africa have been undertaken by AfriChol, the African Cholera Surveillance Network (19). To further understand disease transmission patterns, Amanda Debes from the JHU Bloomberg School of Public Health described a combined clinical and environmental surveillance of Vibrio cholerae for resourcelimited areas that involves testing of clinical specimens with a rapid dipstick assay (crystal V. cholerae; Span Diagnostics Ltd., India), after alkaline peptone water (APW) enrichment, and blotting onto filter paper for subsequent analysis using molecular methods (20,21). This method was successfully used in the far north region of Cameroon and enabled early detection of cases and rapid response (21).…”
mentioning
confidence: 99%